Community Stucture of Fish in Terentang Lake District Sanggau Regency Kalimatan Barat - Hendrianus, Hendrianus; Soetignya, Widadi Padmarsari; Mulyadi, Ahmad (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aims to determine the structure of the fish community in the waters of Lake Terentang. Subah Village, TayanHilir District, Sanggau Regency, West Kalimantan Province. This research was conducted from July to October 2019, by taking 3 sampling points. Sampling was done 3 times at each station; at 08.00 AM -10.00 AM; 12.00 AM - 02.00 PM;05.00 PM -07.00 AM, each repeated 3 times using atrawl (gill net) with a 1.5 inches mesh size, a cast net with 1.4 inchesmesh sizeand a Bubu (traditional fish trap). Plankton sampling uses plankton net and water quality research carried out in situ while doing the fish sampling. The results showed that the fish caught totaling 1728 individuals, 19 species, 16 genera from 9 families. The species that are dominant are from the Cyprinidaefamily(7 species) and then Osphronemidae (3 species) and the least is from the Claridaeand Siluridae each of 1 species. Diversity Index (H ') based on fishing gear ranged from 2.09 to 2.52 with moderate category, Uniformity (E') ranged from 0.83 to 0.89 in the high category and Dominance (C) ranged from 0.11 to 0.26 low category. Plankton abundance obtained a total of 1009 plankton were observed which are divided into 14 species. The results of several parameters of the quality of the Lake Terentang Lake are still suitable for the life of the organism.Kata Kunci : Composition of fish species, diversity index, dominance, uniformity and RLG (Relative Length of Gut)